Accounting for management control - Emmanuel, Clive R.; Otley, David; Merchant, Kenneth (London : International Thomson Business Press, 1997)
This book is divided into five parts: The contexts of management accounting; Accounting for programmed activities; Accounting for non-programmed activities; Aframework for analysis; Case studies.
Keywords: Accounting; Managerial accounting